2019
DOI: 10.1038/s41598-019-55314-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disease, antibiotic treatment and recovery trajectory on the microbiome of farmed seabass (Dicentrarchus labrax)

Abstract: The mucosal surfaces of fish harbour microbial communities that can act as the first-line of defense against pathogens. Infectious diseases are one of the main constraints to aquaculture growth leading to huge economic losses. Despite their negative impacts on microbial diversity and overall fish health, antibiotics are still the method of choice to treat many such diseases. Here, we use 16 rRNA V4 metataxonomics to study over a 6 week period the dynamics of the gill and skin microbiomes of farmed seabass befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 83 publications
10
79
1
Order By: Relevance
“…Furthermore, it was shown that while these communities stabilise during recovery, they do not appear to return to their original state in the short-term (~1 week). In some sh such as sea bass (Dicentrarchus labrax), it has also been shown that recovery over the longer term (~ 3 weeks following oral administration of oxytetracycline) may vary between the different mucosal surfaces, with the communities associated with the skin reported to be more resilient to those of the gills [71]. In support of this, we also observed here a greater disparity in the effects of antibiotic treatment on the gut rather than the skin bacterial communities.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, it was shown that while these communities stabilise during recovery, they do not appear to return to their original state in the short-term (~1 week). In some sh such as sea bass (Dicentrarchus labrax), it has also been shown that recovery over the longer term (~ 3 weeks following oral administration of oxytetracycline) may vary between the different mucosal surfaces, with the communities associated with the skin reported to be more resilient to those of the gills [71]. In support of this, we also observed here a greater disparity in the effects of antibiotic treatment on the gut rather than the skin bacterial communities.…”
Section: Discussionsupporting
confidence: 81%
“…Up to date, there are not studies on the effects of diet on skin mucus microbiota of farmed sh. However, since the feed catabolites are dispersed in the water, and the quality of water is one of the factors that can change the composition of sh microbiotas [28][29][30], it would be interesting to see the dynamics of both gut and skin microbiota in sh fed diets with insect meal.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,36,61], including seabass and seabream [71], have shown remarkable differences in microbial composition and structure across host species and tissues. Additionally, a previous study by our group [72] showed that disease and antibiotic treatment in seabass leads to asymmetrical shifts in skin and gill microbial communities. Therefore, all our statistical analyses were carried out separately for each sh species and tissue.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 84%